Analisis Kualitas Air Laut dan Indeks Pencemaran Berdasarkan Parameteri Fisika-Kimia di Kampung Wuring Kabpaten Sikka - Afika Fitrah; Mariana Sada; Yulimira Syafriati Y.M. Sani (Pro-Life, 2024)
This study aims to determine the quality of seawater in the waters of Wuring Village, Sikka Regency through Physico-Chemical parameters. This research was conducted in the waters of Wuring Village, Sikka Regency and the Regional Health Laboratory of Sikka District. The data used in this study is in the form of primary data and secondary data where primary data is obtained from sampling in the research area and secondary data is obtained from various existing references. The concentration of Turbidity, Dissolved Oxygen (DO), Nitrate and Cyanide at observation stations varies by showing results exceeding the threshold at certain stations and times and showing results meeting quality standards at certain stations and times. The status of sea water quality based on the pollution index method shows that the waters of Wuring Village in the morning are categorized as lightly polluted with an IP value of 3.58, while in the afternoon and evening / night are included in the category of moderately polluted with an IP value of 8.21 and 7,21 Keywords: Quality Status of Sea Water Quality, Coastal Areas and Wuring Village